2022
DOI: 10.1021/acsami.2c16002
|View full text |Cite
|
Sign up to set email alerts
|

Ni/NiO Exsolved Perovskite La0.2Sr0.7Ti0.9Ni0.1O3−δ for Semiconductor-Ionic Fuel Cells: Roles of Electrocatalytic Activity and Physical Junctions

Abstract: A semiconductor-ionic fuel cell (SIFC) is recognized as a promising technology and an alternative approach to reduce the operating temperature of solid oxide fuel cells. The development of alternative semiconductors substituting easily reduced transition metal oxide is a great challenge as high activity and durability should be satisfied simultaneously. In this study, the B-site Ni-doped La0.2Sr0.7Ti0.9Ni0.1O3−δ (LSTN) perovskite is synthesized and used as a potential semiconductor for SIFC. The in situ exsolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
0
14
0
1
Order By: Relevance
“…Perovskite semiconductors have also shown promise as electrolytes for low-temperature CFCs, such as the SrFe 0.2 Ti 0.8 O 3 –ZnO heterostructure demonstrated by Shah et al . Using semiconductor-based materials in ceramic fuel cells offers significant advantages, including enhanced ionic conducting properties and a built-in electric field (BIEF) that prevents electronic short-circuiting and promotes ion transportation. Among these materials, BaTiO 3 , a widely studied perovskite, possesses high dielectric constant and ferroelectric properties, making it suitable for various electronic and electro-optical applications. Using high dielectric materials with large polarizability to develop oxide-ion electrolytes has also emerged. , An exciting strategy was needed to advance CFCs, and this study presents an approach using a BaTiO 3 (BTO) coating, incorporating the wide band gap ion-conducting semiconductor material CeO 2 as a promising electrolyte layer for CFCs. The authors also investigated the surface and interfacial properties of the BTO–CeO 2 interfaces to enhance ionic conductivity and realize a successful fuel cell operation.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite semiconductors have also shown promise as electrolytes for low-temperature CFCs, such as the SrFe 0.2 Ti 0.8 O 3 –ZnO heterostructure demonstrated by Shah et al . Using semiconductor-based materials in ceramic fuel cells offers significant advantages, including enhanced ionic conducting properties and a built-in electric field (BIEF) that prevents electronic short-circuiting and promotes ion transportation. Among these materials, BaTiO 3 , a widely studied perovskite, possesses high dielectric constant and ferroelectric properties, making it suitable for various electronic and electro-optical applications. Using high dielectric materials with large polarizability to develop oxide-ion electrolytes has also emerged. , An exciting strategy was needed to advance CFCs, and this study presents an approach using a BaTiO 3 (BTO) coating, incorporating the wide band gap ion-conducting semiconductor material CeO 2 as a promising electrolyte layer for CFCs. The authors also investigated the surface and interfacial properties of the BTO–CeO 2 interfaces to enhance ionic conductivity and realize a successful fuel cell operation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a new type of cell structure can be constructed by reducing the operating temperature to solve the above two problems. 4,5 The traditional fuel cell is a three-layer structure. Zhu et al reported a new type of cell structure: single-component fuel cell (SCFC), which is composed of a semiconductor and ionic conductor material.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high-temperature operation will increase the requirements for cell modules and increase cell costs. Therefore, a new type of cell structure can be constructed by reducing the operating temperature to solve the above two problems. , …”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor materials play a vital role in the reactions taking place at both electrodes and therefore have specific structural and activity requirements. 11,12 In general, electrode materials must have excellent catalytic oxidation and reduction activity, as well as good stability under high temperature and high humidity conditions. Among these materials, the perovskite La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) oxide has gained wide recognition and usage due to its acceptable hydrogen oxidation/oxygen reduction activity and good tolerance against moisture atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used electrolyte materials in single-component SOCs include Sm 0.2 Ce 0.8 O 2−δ (SDC) and SDC-carbonate. Semiconductor materials play a vital role in the reactions taking place at both electrodes and therefore have specific structural and activity requirements. , In general, electrode materials must have excellent catalytic oxidation and reduction activity, as well as good stability under high temperature and high humidity conditions. Among these materials, the perovskite La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3‑δ (LSCF) oxide has gained wide recognition and usage due to its acceptable hydrogen oxidation/oxygen reduction activity and good tolerance against moisture atmosphere. , Recently, various strategies have been explored to enhance the catalytic activity of electrode materials for both conventional and single-component SOCs. For example, introducing A-site defects in (La 0.6 Sr 0.3 )­CrO 3‑δ hydrogen electrode material has been shown to significantly enhance the concentration of oxygen vacancies, thus improving catalytic activity .…”
Section: Introductionmentioning
confidence: 99%